Enunciative “looping effects” in Discourse Analysis and their legitimating function - Rocha, Décio (2011)
This paper is focused on a discussion on the concept of enunciative looping effects (MAINGUENEAU, 1989), understood as how the text establishes a scene that the enunciative activity simultaneously produces and assumes in order to legitimate itself. The corpus selected for analysis were those discourses in the printed media that deal with videogames in Portuguese and in French, in order to demonstrate how, through the use of the concept mentioned above, a more adequate treatment of the articulation that one verifies between enunciation and what was stated is possible from the analysis of different devices – discursive locution, topography, chronography, ethos, linguistic code – that define a given positioning inside a discursive field.